Signature of a highly spin polarized resonance state at Co2MnSi(0 0 1)/Ag(0 0 1) interfaces - Lidig, Christian; Minar, Jan; Braun, Juergen; Ebert, Hubert; Gloskovskii, Andrei; Kronenberg, Alexander; Klaeui, Mathias; Jourdan, Martin (Journal of Physics D: Applied Physics, 2018)
We investigated interfaces of halfmetallic Co2MnSi(1 0 0) Heusler thin films with Ag(1 0 0), Cr(1 0 0), Cu and Al layers relevant for spin valves by high energy x-ray photoemission spectroscopy (HAXPES). Experiments on Co2MnSi samples with an Ag(1 0 0) interface showed a characteristic spectral shoulder feature close to the Fermi edge, which is strongly diminished or suppressed at Co2MnSi (1 0 0) interfaces with the other metallic layers. This feature is found to be directly related to the Co2MnSi(1 0 0) layer, as reflected by control experiments with reference non-magnetic films, i.e. without the Heusler layer. By comparison with HAXPES calculations, the shoulder feature is identified as originating from an interface state related to a highly spin polarized surface resonance of Co2MnSi (1 0 0).
CRIS-Team Scopus Importer:2023-03-27
Keywords: band structure; Heusler thin films; interface states; photoemission spectroscopy; spintronics